Identifikasi Anomali dan Dampak Perbaikan Sistem Automatic Transfer Switch (ATS) terhadap Kontinuitas Pasokan Listrik di PT. PLN UP3 Tanjung Priok - Koerniawan, Tony; Hasanah, Aas Wasri; Nugraha, Shafa Khairunisa; Kurniawan, Sandi Budi; Yudho, Satrio; Nursita, Ersalia Dewi (Prosiding Seminar Nasional Teknoka, 2025)
Disruptions to the Automatic Transfer Switch (ATS) system can reduce the reliability of the electricity supply, especially for priority customers. This study aims to identify anomalies occurring in the ATS system in the PT. PLN (Persero) UP3 Tanjung Priok area. The methods used include field observations, technical inspections of ATS components, switching time measurements, and estimates of unsupplied energy. Anomalies were found at three locations, namely SMU 110 Jakarta, the Water Management Public Works Sub-Department, and the Sunter Environmental Development Supervisory Agency, with the main damage occurring to the rectifier and ATS module. This damage caused automatic switching failure and interruption of the electricity supply during the repair process, resulting in a total energy loss of 330.640 kWh. After repairs were completed, the entire ATS system resumed functioning with a switching time of < 1 second, in accordance with standards. The results of this study indicate that anomalies in ATS components have a significant impact on the continuity of electricity supply, but can be effectively addressed through appropriate technical repairs.